ERA OF CONJUGATE VACCINES: INTERNATIONAL EXPERIENCE OF SUCCESSFUL APPLICATION - M.V. Fedoseenko; M.G. Galitskaya; L.S. Namazova (Union of pediatricians of Russia, 2008)
The article highlights comparative characteristics of the polysaccharide and conjugate vaccines against pneumococcal infection, meningococcosis and haemophilus influenza. The author stresses the advantage of the conjugate vaccines. The researcher provides the data on the achieved success as to the application of the conjugate vaccines against the said infections abroad and demonstrates a sizable reduction in the morbidity with different forms of pneumococcal infection, resulting from the conjugate pneumococcal vaccine introduced to the immunization program in the developed nations of the world.Key words: pneumococcal infection, meningococcosis, haemophilus influenzae, vaccine, types of vaccines, children.